G71(P) Accuracy of the Strobel's and Modified Strobel's formulae in pH catheter placement in children: A prospective cohort study. (7th April 2014) - Saha, A; Bhaduri, B
Abstract : Introduction and aim: Oesophageal pH monitoring is the gold standard technique for the detection of acid gastro-oesophageal reflux episodes, and correct placement of the catheter is crucial for accuracy of the readings. The Strobel formula is frequently used as a guide to determine distance from the nostrils to the lower oesophageal sphincter (LES). However, this formula was noted to overestimate the pH catheter placement distance, and a modified Strobel formula was introduced for more accuracy. The aim of the study was to compare the accuracy of Strobel formula (SF) and modified Strobel formula (MSF) measurements in the correct placement of the catheter, in children more than 1 year of age. Subjects and methods: A prospective study in children above the age of one year was done to determine the accuracy of these formulae. The length of catheter was calculated using Strobel's and modified Strobel's formulae. The actual catheter placement was adjusted and confirmed either by direct measurement of length at endoscopy and/or confirming its tip position between T8 and T10 level on chest X-ray. This was compared with the predicted position as per the above formulae, and their mean deviation was calculated. Results: 14 children were included in this study. The mean deviation for the Strobel's formula was +6.9(+ 2.8 to 11.0)cm, whereas the mean deviation for the modified Strobel's formula was –0.99(–5.23 to + 3.61)cm. Therefore, our data shows that the SF overestimated the LES distance by an average of 6.9 cm, whereas the MSF underestimated it 0.99 cm on average. Summary and conclusion: This study showed that the Modified Strobel's Formula is more accurate than the Strobel's formula in pH probe placement in children more than 1 year of age. Data from a similarly designed previous study has also shown it to be more accurate in infants less than 1 year of age. We recommend that the Modified Strobel's formula be used in all age groups of children for initial probe placement. However, in order to do a reliable pH study, radiographic confirmation of the catheter tip position must still be considered when using any formula.